The Influence of The Probing Prompting Learning Model on The Development of Students’ Critical Thinking Ability - I Nyoman Sudyana; Didi Sudrajat; Sudadi Sudadi; Husnatul Fitriyah; Syatria Adymas Pranajaya (Journal on Education, 2023)
It still has to be enhanced since students' critical thinking abilities on the subject matter of rotational dynamics and equilibrium of rigid bodies are still an issue. The purpose of this study is to ascertain the impact of the probing prompting learning model on students' capacity for critical thought with regard to the rotational dynamics and equilibrium of rigid bodies content. A total of 90 children from one of schools made up the sample for this study, which was performed there for four weeks in January 2023. The study approach employed was a quasi-experiment with a design for the control group that was not comparable. The Mann Whitney U examine was used to examine the validity of the hypothesis, and the findings revealed that Ho was rejected. The critical thinking abilities of students who study using the probing prompting model are significantly different from those of students who learn using traditional learning. In the experimental class, students' critical thinking scores increased more than those of the control class students. More than 80% of students expressed interest in using the probing prompting learning methodology. This study demonstrates how the probing prompting learning paradigm significantly enhances students' capacity for critical thought